Technical and market evaluation of thermal generation power plants in the Colombia power system - Jorge Silva-Ortega; Jean Carlos Calvo Cervantes; Eliab de Jesus Rodriguez Acosta; Kelly Margarita Berdugo Sarmiento; Idi Amin Isaac MillÃ¡n; Juan Rivera-Alvarado (Institute of Advanced Engineering and Science, 2023)
Thermal power plants are the widely conventional generation unit technology used to produce electricity being controllable and dispatchable. The location of thermal power plants depends on the energy availability conditions of the areas and the capacity to fuels access. Their location and geographical distribution define a high level of concentration in areas defined as thermal districts and its location define reliability, security, availability, and flexibility indices to avoid critical scenario or support system from contingencies. However, in many cases the electrical configuration does not correspond to requirements. This paper links the concentration by political distribution in Colombia and the configuration used in the generating substations to guarantee requirements. The Hirschman-Herfindahl index as a market tool is used to evaluate energy concentration facing representative participation in certain departments of Colombia. Results evidenced configurations and concentration in a study case, results and analysis could be used for planner to promote participation, reliability and promote. The paperâ€™s contribution and conclusions are linked to guide planners towards market and technical tool to evaluate installed capacities, avoid market concentration, and reduce risky scenarios.